Pengaruh Adversity Quotient terhadap Prestasi Akademik Mahasiswa Angkatan 2013 Fakultas Psikologi UIN SGD Bandung - Tesa Nurul Huda; Agus Mulyana (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2017)
The purpose of this research is to know how significant is the influence of adversity quotient to academic achievement. This research used correlational method with causality type. Respondents of the study were 147 students of Faculty of Psychology UIN SGD Bandung year 2013. The samples were 109 people, selected by simple random sampling technique. AQ measured by a Quick Take Adversity Response Profile (ARP) scale that is modified for educational settings. This study used simple regression analysis. Based on data processing using SPSS 20th version, it was obtained sig value (0.029) < α (0.05). This value shows that H0 is rejected, so there is a significant adversity quotient influence to academic achievement. Coefficient of determination equal to 0,044, showing influence of AQ to academic achievement is 4.4%. Therefore AQ is one of the low factor that affect academic achievement.